A Second Look at the Pesticides Initiative Program: Evidence from Senegal - Olivier Cadot; Melise Jaud (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
This paper investigates whether the Pesticides Initiative Program has signicantly affected the export performance of Senegal's horticulture industry. We apply two main microeconometric techniques, difference-in-differences and matching difference-in-differences, to identify the effect of the Pesticides Initiative Program on exports of fresh fruits and vegetables. We use a unique firm-level dataset containing data on sales, employment, and exports by product and destination markets, as well as firm enrolment year, over 2000-2008. The results suggest that while the program had no signicant effect on exports pooled over all products and destinations, it had a positive effect when considering fresh fruits and vegetables exports to the European Union.
Keywords: F13; L15; L25; O13; C23; 330